Franz Kafka por uma literatura realista: a vida reverberada em O processo - Pacheco, Thiago Sampaio (2021)
This dissertation seeks to analyze the novel The Process of Franz Kafka under the possibility of a realistic reading, while considering the fundamental characteristic of humanism, in an attempt to confront the irrationalist tendencies that critics attribute to this work. What is intended is the discussion of a decisive literary and philosophical-social positioning of Kafka's production, through the immanent analysis of the narrative text, as well as facing different critical perspectives, mainly those of the Hungarian philosopher Georg Lukács, published in Critical Realism Today (1969). Dialogging with the critical bases already formulated by Carlos Nelson Coutinho (2005) the intention is the recognition that in The Process contains the most profound consequences of the forms of alienation from capitalism and that, through the criticism of this system, Kafka reveals the important reality of its historical period.